Antidiabetic, antioxidant and anti inflammatory properties of water and n-butanol soluble extracts from Saharian Anvillea radiata in high-fat-diet fed mice. (31st July 2017) - Kandouli, Chouaib; Cassien, Mathieu; Mercier, Anne; Delehedde, Caroline; Ricquebourg, Emilie; Stocker, Pierre; Mekaouche, Mourad; Leulmi, Zineb; Mechakra, Aicha; Thétiot-Laurent, Sophie; Culcasi, Marcel; Pietri, Sylvia
Abstract: Ethnopharmacological relevance: According to Saharian traditional medicine, Anvillea radiata Coss. & Dur. (Asteraceae) has been valued for treating a variety of ailments such as gastro-intestinal, liver and pulmonary diseases, and has gained awareness for its beneficial effect on postprandial hyperglycemia. However, to best of our knowledge, no detailed study of the antidiabetic curative effects of this plant has been conducted yet. Aim of the study: To determine the hypoglycemic and antidiabetic effect of dietary supplementation with Anvillea radiata extracts on high-fat-diet (HFD)-induced obesity and insulin resistance in C57BL/6 J mice in relation with antioxidant, anti-inflammatory, pancreatic beta-cells and skeletal muscle protection, and digestive enzyme inhibiting properties. Materials and methods: Six extracts (water soluble and organic) from aerial parts of the plant were analyzed phytochemically (total phenolic and flavonoid content) and screened for in vitro superoxide (by chemiluminescence) and hydroxyl radical (by electron paramagnetic resonance spin-trapping) scavenging, antioxidant (DPPH, TRAP and ORAC assays), xanthine oxidase, metal chelating, α -amylase and α -glucosidase inhibitory property, and protective effects on copper-induced lipoprotein oxidation. Then selected hydroalcoholic and aqueous extracts were assessed for toxicity in normal human lung fibroblasts and A549 cancer cells using FMCA and MTT assays. Two water-soluble extracts having the best overall properties were assessed for their (i) protective effect at 1−15 µg/mL on metabolic activity of rat insulinoma-derived INS-1 cells exposed to hyperglycemic medium, and (ii) acute hypoglycemic effect on 16-weeks HFD-induced diabetic mice. Then diabetic mice were administered HFD supplemented by extracts (up to 150 mg/kg/day) for 12 additional weeks using standard diet as control and the antidiabetic drug, metformin (150 mg/kg), as positive control. Then the antidiabetic, anti-inflammatory and antioxidant activity of extracts were determined. Results: Of the highly efficient polyphenolics-enriched hydroalcoholic and ethyl acetate extracts, the lyophilized aqueous (AQL) and butanol extracts were not toxic in cells (≤ 400 µg/mL) or when given orally in normal mice (≤ 2000 mg/kg), exerted a dose-dependent hypoglycemic action in diabetic mice, which was maximal at the dose of 150 mg/kg. Upon administering this dose for 12 weeks, both extracts significantly ameliorated body weight control capacity, recovery of plasma glucose and insulin level, reduced oxidative stress in blood, myocardial and skeletal muscles, and improved hyperlipidemic and inflammatory status. Moreover, diabetes-related complications were optimally ameliorated by oral therapy based on halved doses (75 mg/kg) of a mixture of AQL and metformin. Conclusions: Current investigation supports the traditional medicinal usage of Anvillea radiata and suggests that both readily accessible and low-cost bio-extracts have the potency to develop an antihyperglycemic, antihyperlipidemic and protective agent against beta-cells and muscle dysfunction at doses compatible with the common practices of indigenous people for the management of metabolic disorders. Graphical abstract: